Developing an explanatory risk management model to comprehend the employees' intention to leave public sector organization - Carolina Prihandinisari; Azizur Rahman; John Hicks (Journal of Risk and Financial Management, 2020)
This paper reviews research and theory on the important topic of labour turnover resulting from issues related to job performance and/or job satisfaction which have, in turn, been initiated by changes in work motivation. We focus on labour turnover in the public sector-a neglected area of public administration research-and propose an explanatory model of the development of the intention to leave an organization. The model first describes the relationships between work motivation and job performance and/or job satisfaction. It then explains how changes in performance and/or satisfaction result in the formation of an intention to leave public service employment. The paper concludes by identifying key areas for future research.
Keywords: 330; financial incentives; intention to leave; job performance; job satisfaction; public service motivation